Elementary School Students Numeration Ability - Suciyati Suciyati; Dedy Rosadi; Mariamah Mariamah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
Numerical ability is one of the important skills that must be mastered by students as a provision in solving everyday problems. It is also undeniable that the numeracy skills of elementary school students are still far from expectations. Various problems arise in learning mathematics such as the gap in the numeracy abilities of different students. The purpose of this study is to describe the numeracy skills of upper-class students in elementary schools. This type of research is descriptive research with the research subjects are 4th to 6th grade students at SDN Talabiu, Bima, West Nusa Tenggara. The instrument used is in the form of multiple choice test questions, totaling 10 numbers which have been validated by experts by asking for input from colleagues from the evaluation field and the field of mathematics. In addition, this instrument is also a modified finished instrument that has been approved by the developer. The data were analyzed using the percentage formula to determine the category of students' abilities. Based on the results of research and data analysis, information was obtained that the numeracy skills of upper-class students at SD Negeri Talabiu can be grouped into 4 categories, namely the High category with a percentage of 16%, the Moderate Category with a percentage of 62%, the less category with a percentage of 14% and the very low category. with a percentage of 8%. The contribution of the results of this study is as a reference for teachers and schools in relation to the state of students' numeracy abilities so that they can apply innovative and creative learning